More GP contacts and poorer health of informal caregivers with low socioeconomic status in Germany: results from the population-based DEGS1 and the cross-sectional GPCare-1 study. Issue 12 (30th December 2021) - Gavrilov, Boris; Schmidt, Manuela; Kasten, Stefanie; Sommer, Samira; Hunzelar, Carmen; Bockheim, Florian; Paños-Willuhn, Joana; Offenberg, Luisa; Oberholz, Maja; Ikar, Nur; Weltermann, Birgitta
Abstract : Objectives: Informal caregivers are known to have poorer mental health. Risk factors for caregiver burden include low education, female gender, cohabitation with the care recipient and lack of resources. General practitioners (GPs) have an important role in supporting caregivers. Drawing on data from two surveys, associations between caregivers' socioeconomic status (SES), psychophysical health and GP contacts are analysed. Design: Cross-sectional study. The study draws on data from two surveys (German Health Interview and Examination Survey for Adults, DEGS1 and General Practice Care-1, GPCare-1). Setting: Germany. Participants: DEGS1: German general population (18+ years) n=7987. GPCare-1: general practice patients (18+ years) n=813. Primary outcome: Psychophysical health, GP contacts and communication. Methods: Using representative DEGS1 data, the prevalence of informal caregivers, caregivers' burden, chronic stress, various health conditions and frequency of GP contacts were evaluated stratified by SES. Data from the GPCare-1 study addressed caregivers' experiences and communication preferences with GPs. Results: In the DEGS1, the prevalence of caregivers was 6.5%. Compared with non-caregivers, caregivers scored significantly higher for chronic stress (15.45 vs 11.90), self-reported poor health (37.6% vs 23.7%) and GP visits last year (3.95 vs 3.11), while lifestyle and chronic diseases were similar. Compared with caregivers with medium/high SES, those with low SES had a significantly lower prevalence of high/medium caregiver burden (47.9% vs 67.7%) but poorer self-reported health (56.9% vs 33.0%), while other characteristics did not differ. In the GPCare-1 study, the prevalence of caregivers was 12.6%. The majority of them felt that their GP takes their problems seriously (63.6%) without difference by SES. Conclusion: Caregivers with low SES constitute an especially high-risk group for psychological strain, requiring special GP attention to support their needs.